(untitled) (Journal of the College of Basic Education, 2022)
The research was available in its topic marked by (Grammarians’ Errors in the Light of Sibawayh’s Book, An Investigative Critical Study) on a term that the scholars did not touch except casually in the multiplication of their works and studies, as it happened to me when delving into it that it is soft and unsaturated in a way that heals the researcher’s thirst. My grandfather’s arms, and I made to track every issue of error in detail, investigation and criticism, so I concluded a number of scientific results that I wrote down in the conclusion of the research except for what I entrusted the issue of finding out to the researchers themselves, and perhaps one of the most important results that I came across and investigated is that the issues of (error) Covered in the multiplications of Sibawayh’s book, may God have mercy on him, are not in one condition, as some of them are reasonable and acceptable.